Comparisons between perivascular adipose tissue and the endothelium in their modulation of vascular tone. (18th November 2016) - Zaborska, K E; Wareing, M; Austin, C
Abstract : The endothelium is an established modulator of vascular tone; however, the recent discovery of the anti‐contractile nature of perivascular adipose tissue (PVAT) suggests that the fat, which surrounds many blood vessels, can also modulate vascular tone. Both the endothelium and PVAT secrete vasoactive substances, which regulate vascular function. Many of these factors are common to both the endothelium and PVAT; therefore, this review will highlight the potential shared mechanisms in the modulation of vascular tone. Endothelial dysfunction is a hallmark of many vascular diseases, including hypertension and obesity. Moreover, PVAT dysfunction is now being reported in several cardio‐metabolic disorders. Thus, this review will also discuss the mechanistic insights into endothelial and PVAT dysfunction in order to evaluate whether PVAT modulation of vascular contractility is similar to that of the endothelium in health and disease. Linked Articles: This article is part of a themed section on Molecular Mechanisms Regulating Perivascular Adipose Tissue – Potential Pharmacological Targets? To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.20/issuetoc